Perfil fermentativo e bromatológico de silagens de aveia branca e jiggs com adição de torta de oliva - Fernandes, Renata Amanda Aguilar (2021)
The aim was to evaluate whether temperate or tropical grass silages with the addition of different levels of the olive oil cake alter the nutritional and fermentative profile. The treatments were in four levels of the additive in silage: exclusive silage of White Oat or addition of 6, 12, 18 e 24% of olive oil cake and exclusive silage of Jiggs or addition of 6, 12, and 18% olive oil cake. The microsilos were stored for 70 days and at the time of opening to report fermentative profile, pH, buffering capacity, losses by gases and effluents were evaluated and later water soluble carbohydrate (WSC), ammoniacal nitrogen (NH3-N), lactic acid (LA), acetic acid (AA), propionic acid (PA), butyric acid (BA). The chemical composition was obtained from the analysis of dry matter (DM), organic matter (OM), ash, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), crude fat (CF) protein and carbohydrate fractionation and in vitro dry matter digestibility (IVDMD). In Jiggs silage in vitro degradation kinetics was evaluated. Olive oil cake in white oat silage had an increased linear effect on the content of DM, OM, NDF, ADF, ADL and CF. In the fermentative profile, only the production of effluents reported a significant difference (p<0,05) and with an increasing linear effect. In Jiggs silage, the contents of DM, OM, NDF, ADF, ADL were higher with the addition of olive oil cake. While the content of ash, CP, WSC, and IVDMD decreased and in the fermentative profile the variables buffering capacity, LA, PA, BA, and effluents reported significant differences. In oat silage the fermentative profile was like the material without adding the by-product, therefore, it did not interfere in the improvement of fermentation. In the Jiggs silage, the fermentation process was satisfactory, however, the addition of olive oil cake increased the fibrous fraction. Thus, the inclusion of olive cake in white oat silage did not alter the fermentative profile, while the chemical composition was changed. In the Jiggs silage the fermentation profile was changed, and the process was satisfactory, the chemical composition was also changed, increasing the fibrous fraction. As the inclusion of the olive cake in both silages had a linear effect, all levels are indicated for inclusion.